Species of coagulase positive Staphylococcus isolated from clinical specimens - Lulitanond, Aroonlug; Chanawong, Aroonwadee; Sribenjalux, Pipat; Pongchanwit, Poompan; Peongthean, Sarinya (Archives of Allied Health Sciences, 2005)
abtract not available